data.pi

Instances and theorems on pi types #

This file provides basic definitions and notation instances for Pi types.

Instances of more sophisticated classes are defined in pi.lean files elsewhere.

1, 0, +, *, -, ⁻¹, and / are defined pointwise.

@[protected, instance]
def pi.has_zero {I : Type u} {f : I → Type v₁} [Π (i : I), has_zero (f i)] :
has_zero (Π (i : I), f i)
Equations
@[protected, instance]
def pi.has_one {I : Type u} {f : I → Type v₁} [Π (i : I), has_one (f i)] :
has_one (Π (i : I), f i)
Equations
@[simp]
theorem pi.zero_apply {I : Type u} {f : I → Type v₁} (i : I) [Π (i : I), has_zero (f i)] :
0 i = 0
@[simp]
theorem pi.one_apply {I : Type u} {f : I → Type v₁} (i : I) [Π (i : I), has_one (f i)] :
1 i = 1
theorem pi.one_def {I : Type u} {f : I → Type v₁} [Π (i : I), has_one (f i)] :
1 = λ (i : I), 1
theorem pi.zero_def {I : Type u} {f : I → Type v₁} [Π (i : I), has_zero (f i)] :
0 = λ (i : I), 0
@[simp]
theorem pi.const_one {α : Type u_1} {β : Type u_2} [has_one β] :
= 1
@[simp]
theorem pi.const_zero {α : Type u_1} {β : Type u_2} [has_zero β] :
= 0
@[simp]
theorem pi.zero_comp {α : Type u_1} {β : Type u_2} {γ : Type u_3} [has_zero γ] (x : α → β) :
0 x = 0
@[simp]
theorem pi.one_comp {α : Type u_1} {β : Type u_2} {γ : Type u_3} [has_one γ] (x : α → β) :
1 x = 1
@[simp]
theorem pi.comp_zero {α : Type u_1} {β : Type u_2} {γ : Type u_3} [has_zero β] (x : β → γ) :
x 0 = (x 0)
@[simp]
theorem pi.comp_one {α : Type u_1} {β : Type u_2} {γ : Type u_3} [has_one β] (x : β → γ) :
x 1 = (x 1)
@[protected, instance]
def pi.has_mul {I : Type u} {f : I → Type v₁} [Π (i : I), has_mul (f i)] :
has_mul (Π (i : I), f i)
Equations
@[protected, instance]
def pi.has_add {I : Type u} {f : I → Type v₁} [Π (i : I), has_add (f i)] :
has_add (Π (i : I), f i)
Equations
@[simp]
theorem pi.add_apply {I : Type u} {f : I → Type v₁} (x y : Π (i : I), f i) (i : I) [Π (i : I), has_add (f i)] :
(x + y) i = x i + y i
@[simp]
theorem pi.mul_apply {I : Type u} {f : I → Type v₁} (x y : Π (i : I), f i) (i : I) [Π (i : I), has_mul (f i)] :
(x * y) i = (x i) * y i
theorem pi.mul_def {I : Type u} {f : I → Type v₁} (x y : Π (i : I), f i) [Π (i : I), has_mul (f i)] :
x * y = λ (i : I), (x i) * y i
theorem pi.add_def {I : Type u} {f : I → Type v₁} (x y : Π (i : I), f i) [Π (i : I), has_add (f i)] :
x + y = λ (i : I), x i + y i
@[simp]
theorem pi.const_add {α : Type u_1} {β : Type u_2} [has_add β] (a b : β) :
+ = (a + b)
@[simp]
theorem pi.const_mul {α : Type u_1} {β : Type u_2} [has_mul β] (a b : β) :
a) * = (a * b)
theorem pi.mul_comp {α : Type u_1} {β : Type u_2} {γ : Type u_3} [has_mul γ] (x y : β → γ) (z : α → β) :
(x * y) z = (x z) * y z
theorem pi.add_comp {α : Type u_1} {β : Type u_2} {γ : Type u_3} [has_add γ] (x y : β → γ) (z : α → β) :
(x + y) z = x z + y z
@[simp]
theorem pi.bit0_apply {I : Type u} {f : I → Type v₁} (x : Π (i : I), f i) (i : I) [Π (i : I), has_add (f i)] :
bit0 x i = bit0 (x i)
@[simp]
theorem pi.bit1_apply {I : Type u} {f : I → Type v₁} (x : Π (i : I), f i) (i : I) [Π (i : I), has_add (f i)] [Π (i : I), has_one (f i)] :
bit1 x i = bit1 (x i)
@[protected, instance]
def pi.has_inv {I : Type u} {f : I → Type v₁} [Π (i : I), has_inv (f i)] :
has_inv (Π (i : I), f i)
Equations
@[protected, instance]
def pi.has_neg {I : Type u} {f : I → Type v₁} [Π (i : I), has_neg (f i)] :
has_neg (Π (i : I), f i)
Equations
@[simp]
theorem pi.neg_apply {I : Type u} {f : I → Type v₁} (x : Π (i : I), f i) (i : I) [Π (i : I), has_neg (f i)] :
(-x) i = -x i
@[simp]
theorem pi.inv_apply {I : Type u} {f : I → Type v₁} (x : Π (i : I), f i) (i : I) [Π (i : I), has_inv (f i)] :
x⁻¹ i = (x i)⁻¹
theorem pi.neg_def {I : Type u} {f : I → Type v₁} (x : Π (i : I), f i) [Π (i : I), has_neg (f i)] :
-x = λ (i : I), -x i
theorem pi.inv_def {I : Type u} {f : I → Type v₁} (x : Π (i : I), f i) [Π (i : I), has_inv (f i)] :
x⁻¹ = λ (i : I), (x i)⁻¹
theorem pi.const_inv {α : Type u_1} {β : Type u_2} [has_inv β] (a : β) :
a)⁻¹ =
theorem pi.const_neg {α : Type u_1} {β : Type u_2} [has_neg β] (a : β) :
- = (-a)
theorem pi.inv_comp {α : Type u_1} {β : Type u_2} {γ : Type u_3} [has_inv γ] (x : β → γ) (y : α → β) :
x⁻¹ y = (x y)⁻¹
theorem pi.neg_comp {α : Type u_1} {β : Type u_2} {γ : Type u_3} [has_neg γ] (x : β → γ) (y : α → β) :
(-x) y = -x y
@[protected, instance]
def pi.has_sub {I : Type u} {f : I → Type v₁} [Π (i : I), has_sub (f i)] :
has_sub (Π (i : I), f i)
Equations
@[protected, instance]
def pi.has_div {I : Type u} {f : I → Type v₁} [Π (i : I), has_div (f i)] :
has_div (Π (i : I), f i)
Equations
@[simp]
theorem pi.div_apply {I : Type u} {f : I → Type v₁} (x y : Π (i : I), f i) (i : I) [Π (i : I), has_div (f i)] :
(x / y) i = x i / y i
@[simp]
theorem pi.sub_apply {I : Type u} {f : I → Type v₁} (x y : Π (i : I), f i) (i : I) [Π (i : I), has_sub (f i)] :
(x - y) i = x i - y i
theorem pi.div_def {I : Type u} {f : I → Type v₁} (x y : Π (i : I), f i) [Π (i : I), has_div (f i)] :
x / y = λ (i : I), x i / y i
theorem pi.sub_def {I : Type u} {f : I → Type v₁} (x y : Π (i : I), f i) [Π (i : I), has_sub (f i)] :
x - y = λ (i : I), x i - y i
theorem pi.sub_comp {α : Type u_1} {β : Type u_2} {γ : Type u_3} [has_sub γ] (x y : β → γ) (z : α → β) :
(x - y) z = x z - y z
theorem pi.div_comp {α : Type u_1} {β : Type u_2} {γ : Type u_3} [has_div γ] (x y : β → γ) (z : α → β) :
(x / y) z = x z / y z
@[simp]
theorem pi.const_sub {α : Type u_1} {β : Type u_2} [has_sub β] (a b : β) :
- = (a - b)
@[simp]
theorem pi.const_div {α : Type u_1} {β : Type u_2} [has_div β] (a b : β) :
/ = (a / b)
def pi.single {I : Type u} {f : I → Type v₁} [decidable_eq I] [Π (i : I), has_zero (f i)] (i : I) (x : f i) (i_1 : I) :
f i_1

The function supported at i, with value x there.

Equations
• x = x
@[simp]
theorem pi.single_eq_same {I : Type u} {f : I → Type v₁} [decidable_eq I] [Π (i : I), has_zero (f i)] (i : I) (x : f i) :
x i = x
@[simp]
theorem pi.single_eq_of_ne {I : Type u} {f : I → Type v₁} [decidable_eq I] [Π (i : I), has_zero (f i)] {i i' : I} (h : i' i) (x : f i) :
x i' = 0
@[simp]
theorem pi.single_eq_of_ne' {I : Type u} {f : I → Type v₁} [decidable_eq I] [Π (i : I), has_zero (f i)] {i i' : I} (h : i i') (x : f i) :
x i' = 0

Abbreviation for single_eq_of_ne h.symm, for ease of use by simp.

@[simp]
theorem pi.single_zero {I : Type u} {f : I → Type v₁} [decidable_eq I] [Π (i : I), has_zero (f i)] (i : I) :
0 = 0
theorem pi.single_apply {I : Type u} [decidable_eq I] {β : Type u_1} [has_zero β] (i : I) (x : β) (i' : I) :
x i' = ite (i' = i) x 0

On non-dependent functions, pi.single can be expressed as an ite

theorem pi.single_comm {I : Type u} [decidable_eq I] {β : Type u_1} [has_zero β] (i : I) (x : β) (i' : I) :
x i' = x i

On non-dependent functions, pi.single is symmetric in the two indices.

theorem pi.apply_single {I : Type u} {f : I → Type v₁} {g : I → Type v₂} [decidable_eq I] [Π (i : I), has_zero (f i)] [Π (i : I), has_zero (g i)] (f' : Π (i : I), f ig i) (hf' : ∀ (i : I), f' i 0 = 0) (i : I) (x : f i) (j : I) :
f' j x j) = (f' i x) j
theorem pi.apply_single₂ {I : Type u} {f : I → Type v₁} {g : I → Type v₂} {h : I → Type v₃} [decidable_eq I] [Π (i : I), has_zero (f i)] [Π (i : I), has_zero (g i)] [Π (i : I), has_zero (h i)] (f' : Π (i : I), f ig ih i) (hf' : ∀ (i : I), f' i 0 0 = 0) (i : I) (x : f i) (y : g i) (j : I) :
f' j x j) y j) = (f' i x y) j
theorem pi.single_op {I : Type u} {f : I → Type v₁} [decidable_eq I] [Π (i : I), has_zero (f i)] {g : I → Type u_1} [Π (i : I), has_zero (g i)] (op : Π (i : I), f ig i) (h : ∀ (i : I), op i 0 = 0) (i : I) (x : f i) :
(op i x) = λ (j : I), op j x j)
theorem pi.single_op₂ {I : Type u} {f : I → Type v₁} [decidable_eq I] [Π (i : I), has_zero (f i)] {g₁ : I → Type u_1} {g₂ : I → Type u_2} [Π (i : I), has_zero (g₁ i)] [Π (i : I), has_zero (g₂ i)] (op : Π (i : I), g₁ ig₂ if i) (h : ∀ (i : I), op i 0 0 = 0) (i : I) (x₁ : g₁ i) (x₂ : g₂ i) :
(op i x₁ x₂) = λ (j : I), op j x₁ j) x₂ j)
theorem pi.single_injective {I : Type u} (f : I → Type v₁) [decidable_eq I] [Π (i : I), has_zero (f i)] (i : I) :
@[simp]
theorem pi.single_inj {I : Type u} (f : I → Type v₁) [decidable_eq I] [Π (i : I), has_zero (f i)] (i : I) {x y : f i} :
x = y x = y
theorem function.extend_one {α : Type u_1} {β : Type u_2} {γ : Type u_3} [has_one γ] (f : α → β) :
1 = 1
theorem function.extend_zero {α : Type u_1} {β : Type u_2} {γ : Type u_3} [has_zero γ] (f : α → β) :
0 = 0
theorem function.extend_add {α : Type u_1} {β : Type u_2} {γ : Type u_3} [has_add γ] (f : α → β) (g₁ g₂ : α → γ) (e₁ e₂ : β → γ) :
(g₁ + g₂) (e₁ + e₂) = g₁ e₁ + g₂ e₂
theorem function.extend_mul {α : Type u_1} {β : Type u_2} {γ : Type u_3} [has_mul γ] (f : α → β) (g₁ g₂ : α → γ) (e₁ e₂ : β → γ) :
(g₁ * g₂) (e₁ * e₂) = g₁ e₁) * g₂ e₂
theorem function.extend_neg {α : Type u_1} {β : Type u_2} {γ : Type u_3} [has_neg γ] (f : α → β) (g : α → γ) (e : β → γ) :
(-g) (-e) = - e
theorem function.extend_inv {α : Type u_1} {β : Type u_2} {γ : Type u_3} [has_inv γ] (f : α → β) (g : α → γ) (e : β → γ) :
e⁻¹ = g e)⁻¹
theorem function.extend_div {α : Type u_1} {β : Type u_2} {γ : Type u_3} [has_div γ] (f : α → β) (g₁ g₂ : α → γ) (e₁ e₂ : β → γ) :
(g₁ / g₂) (e₁ / e₂) = g₁ e₁ / g₂ e₂
theorem function.extend_sub {α : Type u_1} {β : Type u_2} {γ : Type u_3} [has_sub γ] (f : α → β) (g₁ g₂ : α → γ) (e₁ e₂ : β → γ) :
(g₁ - g₂) (e₁ - e₂) = g₁ e₁ - g₂ e₂
theorem function.surjective_pi_map {I : Type u} {f : I → Type v₁} {g : I → Type v₂} {F : Π (i : I), f ig i} (hF : ∀ (i : I), function.surjective (F i)) :
function.surjective (λ (x : Π (i : I), f i) (i : I), F i (x i))
theorem function.injective_pi_map {I : Type u} {f : I → Type v₁} {g : I → Type v₂} {F : Π (i : I), f ig i} (hF : ∀ (i : I), function.injective (F i)) :
function.injective (λ (x : Π (i : I), f i) (i : I), F i (x i))
theorem function.bijective_pi_map {I : Type u} {f : I → Type v₁} {g : I → Type v₂} {F : Π (i : I), f ig i} (hF : ∀ (i : I), function.bijective (F i)) :
function.bijective (λ (x : Π (i : I), f i) (i : I), F i (x i))
theorem subsingleton.pi_single_eq {I : Type u} {α : Type u_1} [decidable_eq I] [subsingleton I] [has_zero α] (i : I) (x : α) :
x = λ (_x : I), x